1976
DOI: 10.1002/pen.760160311
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive processes in the shear crystallization of poly(ethylene oxide)

Abstract: The crystallization behavior of samples of poly(ethylene oxide) of varying molecular weights and molecular weight distributions has been studied under varying conditions of shear rate and temperature. These experiments have been carried out in two devices. One is a shearing parallel‐plate instrument that allows direct observation of the crystallizing medium. The other is a shearing concentric‐cylinder dilatometer. In general, shear enhanced the rates of crystallization and nucleation. However, conditions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…The apparatus used in these experiments has been explained in detail elsewhere [ 12, 13,161. It is, therefore, only necessary here to provide a summary of modifications made to the instrument prior to these experiments and present a brief description of the apparatus.…”
Section: Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparatus used in these experiments has been explained in detail elsewhere [ 12, 13,161. It is, therefore, only necessary here to provide a summary of modifications made to the instrument prior to these experiments and present a brief description of the apparatus.…”
Section: Apparatusmentioning
confidence: 99%
“…A second instrument was used in this work to measure nucleation rates in a polymer sample under shear. The apparatus, which is described elsewhere [ 13,211, is a parallel-plate viscometer mounted on the stage of a polarizing microscope. Both plates are made of glass and nuclei are counted directly by a photographic technique.…”
Section: Apparatusmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32][33][34] The earliest work was reported by Treloar and Gent, who observed a decrease in the onset of crystallization for cross-linked natural rubber with increasing extension ratio. [22,23] Fritzsche et al investigated the crystallization kinetics of poly(ethylene oxide), PEO, under varying condition of shear rate and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] Fritzsche et al investigated the crystallization kinetics of poly(ethylene oxide), PEO, under varying condition of shear rate and temperature. [25,26] They found that the kinetics of the crystallization process was altered by shear, as indicated by a decrease in induction time and an elevation of the Avrami exponent. Haas and Maxwell studied the kinetics of crystallization for polyethylene, PE, under stress.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon, apparently entailing a heterogeneous nucleation process, may only in extremely few cases be the result of lattice plane epitaxial crystallization due to proper matching of the lattice parameters of the additive with those of the crystallizing phase. It has been well recognized that flow is a significant variable affecting both the crystallization of polymers from their molten state and the resulting morphology [22,23,24,25,26]. It has been well recognized that flow is a significant variable affecting both the crystallization of polymers from their molten state and the resulting morphology [22,23,24,25,26].…”
mentioning
confidence: 99%